Effect of Green Color Therapy on Blood Pressure Reduction in Elderly With Hypertension at Dungaliyo Health Center - Nurliah Nurliah; Nikmawati puluhulawa; Masni A. Karim (Journal of Community Health Provision, 2022)
Hypertension is a health problem that is quite dangerous in the world, because hypertension is a major risk factor that leads to cardiovascular diseases such as heart attack, heart failure, stroke and kidney disease. The design of this study used a quasi-experimental using a paired T-test. By involving the control group and the intervention group, sampling using purposive sampling, obtained 20 respondents, then given green color therapy. The results showed that the p value was 0.001 (p <0.05), which means that there is a significant effect. It can be concluded that there is an effect of green color therapy on reducing blood pressure in the elderly with hypertension at the Dungaliyo Health Center. So it is hoped that green color therapy should be given to reduce blood pressure in the elderly with hypertension.